Strategic Mapping of Sharia Fintech Development in Indonesia: A SWOT-Based Analysis - Luthfi Hidayat Siregar; Saparuddin Siregar; Muhammad Syahbudi (UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines sharia fintech development in Medan City, Indonesia, amid growing fintech adoption and persistent concerns about literacy, trust, and cybersecurity in urban financial ecosystems. Using a qualitative descriptive design with SWOT scoring, data were collected from 25 purposively selected informants (academics, active users, and sharia fintech practitioners) through open-ended questionnaires and semi-structured interviews, supported by document and literature review. Findings from the IFAS/IFE and EFAS/EFE matrices indicate a supportive internal environment (IFAS = 3.000000) and a favorable external environment (EFAS = 3.543854), positioning Medan in Cell I of the IE matrix (Growth). Key strengths center on perceived sharia compliance and the availability of sharia-based digital financial products, while major constraints include weak regulatory socialization, low public literacy, and uneven IT infrastructure. External threats are dominated by cybersecurity vulnerabilities, conventional fintech dominance, and persistent perceptions that sharia fintech is indistinguishable from conventional services. The strategic map suggests that sustainable growth requires “vertical integration” interpreted as institutional consolidation—strengthening governance and sharia assurance, literacy and user education, security-by-design practices, and reliable service delivery. These priorities align with POJK-based market conduct and the sharia parameters articulated in DSN–MUI fatwas, supporting user trust and the ethical objective of protecting wealth (ḥifẓ al-māl).Keywords: sharia fintech; SWOT analysis; institutional trust; cybersecurity; Medan City